Visualizing the lymphatic vessels and flow with high-resolution ultrasonography and microvascular flow imaging - Joep J. J. Vullings; Caroline van Schaik; Jurgen J. Fütterer; Chris L. de Korte; Willemijn M. Klein (Ultrasonography, 2023)
Imaging of the lymphatic system has always encountered difficulties, such as high costs, timeconsuming procedures, and low-resolution images. Each method of imaging provides its own challenges. The use of high-resolution ultrasonography (HR-US) and microvascular flow imaging (MVFI) may prove to be the most effective method for visualizing the superficial lymphatic vessels. This study investigated the utilization of HR-US and MVFI in imaging inguinal lymph nodes and vessels, as well as the innovative use of an intranodal saline injection that acted as a contrast agent. This technical note aims to demonstrate that HR-US and MVFI, in combination with an intranodal saline injection, are applicable to the dynamic imaging of superficial inguinal lymph nodes and vessels.